Efficacy of Phaleria macrocarpa crude extract to control black apple snail Pomacea maculata Perry - Roonjho, Abdul Rehman; Muhamad Awang, Rita; Mokhtar, Anis Syahirah; Asib, Norhayu (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The highest saponin contents 82.3% to 82.4% were detected in fruits extract of Phaleria macrocarpa followed by 75.2% to 75.7%. in leaves extract. In terms of mortality, 100 % mortality was observed at 1000 and 750 ppm concentration of fruits and leaves extract after exposure of 48 hours. Similarly, in terms of leaves area and weight consumption, 1000, 750 and 500 ppm concentrations of both crude extracts were also not significantly different from positive control niclosamide.